Folic acid induced nephropathy in BALB/C mice (Indian Journal of Veterinary Pathology, 2025)
The present study was conducted to learn about the various pathological changes due to folic acid-induced Renal changes in mice, which is a widely used experimental model to study the mechanisms underlying kidney fibrosis. Following high-dose folic acid administration, acute kidney injury is rapidly induced, primarily affecting the tubular epithelium. Clinical pathology, macroscopic, and microscopic changes with Hematoxylin & Eosin and special stains such as Masson Trichrome Stain fibrous tissue proliferation. Along with fibronectin, α-SMA, and Smad expression in the progression of Kidney fibrosis. Taken together, our findings might serve as a rationale for developing prospective innovative renal fibrosis. This present study's finding serves as a pathological change with the marker identification, affecting Renal disease progression.